Evaluation of the seismic vulnerability of the "Moche" highway bridge located on the pe1n national highway using the capacity spectrum method - Escudero Alcantara, Jonathan Gianpatrick (2022)
In active seismic zones, such as the Peruvian coast, tools for predicting the potential negative impacts of earthquakes are essential for planning mitigation, emergency, and recovery of transportation facilities. For instance, the capacity of a road bridge network after a seismic event to carry traffic flow depends on the degree of expected damage and the related repair costs and downtime. This paper determines the degree of vulnerability of highway bridges to the action of probable earthquakes during the structure's lifetime by applying the capacity spectrum assessment method known as FRACAS (FRAgility through CApacity Spectrum assessment). This approach allows fragility curves to be obtained from analyzing a structure subjected to a series of seismic records of different characteristics. In this way, the method can explain the effect of variability in seismic demand and structural characteristics on the damage statistics simulated for the type of structure and evaluate the associated uncertainty in predicting fragility. As a case study, it is applied the methodology described in the evaluation of the Moche bridge, located in the region of La Libertad (Peruvian coast), which is in an Operational damage state according to an in situ inspection. From the seismic vulnerability assessment, it is obtained that until earthquakes with accelerations of 1.7g, the Moche bridge has a 60% probability of incursion into a Life Safety damage state, being the probability of incursion into a Collapse damage state less than 10%. This methodology is recommended to determine the reliability of bridges, considering the cumulative damage due to probable seismic events during the bridges' lifetime.